Silica Gel Powder Catalyzed Stereoselective Synthesis of Dialkyl 1,1-Diacetyl-8a-hydroy-8-oxo-1,2,8,8atetrahydrocyclopenta[ a]indene-2,3-dicarboxylates from the Reaction of Dialkyl 2-(1-Acetyl-2-oxopropyl)-3-(tributylphosphoranylidene) - SALMANPOUR, SADEGH; AHMADI, EBRAHIM; KHOSRAVI, NARGESS; RAMAZANI, ALI (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1:1 intermediates produced in the reaction between tributylphosphine and dialkyl acetylenedicarboxylates by acetylacetone leads to sterically congested phosphorus ylides. Silica gel powder was found to catalyze intermolecular reaction of the sterically congested phosphorus ylides with indene-1,2,3-trione in solvent-free system under thermal and microwave conditions.